A flux for smelting ultrafine scrap copper particles, a preparation method and a use method thereof

By using flux composed of aluminum fluoride, calcium fluoride and other fluoride during the smelting of ultra-fine waste copper particles, the problem of difficulty in smelting of ultra-fine waste copper particles is solved, and efficient copper recycling is achieved.

CN118854110BActive Publication Date: 2025-04-25JINTIAN COPPER GROUP CORP NINGBO
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411332617.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2025-04-25
Estimated Expiration
2044-09-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively smel ultrafine waste copper particles, resulting in low recovery rate.

Method used

A flux is used, which consists of aluminum fluoride, calcium fluoride, borax, sodium carbonate and sodium chloride. Through the synergistic action of these components, the melting point of the slag is reduced, the copper oxide shell layer is peeled off, and the smelting rate of copper particles is increased.

Benefits of technology

It realizes efficient smelting and recycling of ultra-fine waste copper particles, significantly improving the copper recovery rate, and ensuring the safety and harmlessness of the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118854110B_ABST
    Figure CN118854110B_ABST
Patent Text Reader

Abstract

This invention relates to a flux for smelting ultrafine scrap copper particles, its preparation method, and its application method. The flux components, by weight percentage, include: 10%-50% aluminum fluoride (AlF3), 10%-50% calcium fluoride (CaF2), 5%-20% borax (Na2B4O7), and 10%-40% sodium carbonate (Na2CO3); the balance is sodium chloride (NaCl). The preparation method involves uniformly mixing aluminum fluoride, calcium fluoride, borax, sodium carbonate, and sodium chloride. The application method involves, after starting the furnace, first adding a certain amount of scrap bronze to the smelting furnace, melting it, and then adding ultrafine scrap copper particles mixed with the flux, stirring intermittently to achieve the smelting of the ultrafine scrap copper particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metallurgical casting, and in particular to a flux for smelting ultrafine scrap copper particles, a preparation method and a use method thereof. Background Art

[0002] Brass is an alloy product composed of copper and zinc as the main elements, and other trace elements. It is divided into ordinary brass and special brass, and is used in all aspects of industry and home. However, after a period of use, the copper alloy needs to be recycled because the main workpiece or home product is scrapped.

[0003] In the non-ferrous metal smelting process, the slag (also called furnace ash, or furnace ash slag) produced after the secondary recovery of scrap copper alloy smelting is crushed and recovered. Some copper particles have a diameter of less than 0.1mm. When they are added to the power frequency furnace for smelting again, they basically cannot be melted, resulting in these copper particles being unable to be added to the recycling smelting. Through analysis, there are several reasons why such copper particles cannot be melted:

[0004] 1. Oxidation of copper particles. Copper oxide exists on the surface of copper particles (see Figure 1 ), which makes the melting point of this part of copper particles around 1440℃, which is relatively high;

[0005] 2. Copper particles with a particle size of less than 0.1 mm are in close contact with each other, and heat cannot enter the interior, resulting in the formation of "copper bags" during the smelting process, which seriously restricts production efficiency;

[0006] 3. The slag contains ceramics and other metal powders, which cannot be melted at normal temperatures, increasing the difficulty of smelting.

[0007] How to improve the recovery rate of ultrafine scrap copper particles is an urgent task for smelting and casting workers. In view of the current difficulties in smelting ultrafine copper sand in batches, it is necessary to develop targeted copper sand smelting processes and fluxes.

[0008] In view of this, the present invention is proposed. Summary of the invention

[0009] The first purpose of the present invention is to provide a flux for smelting ultrafine scrap copper particles in view of one of the deficiencies of the current technology, thereby solving the problem that the existing ultrafine scrap copper particles are difficult to melt.

[0010] The second object of the present invention is to provide a method for preparing a flux for smelting ultrafine scrap copper particles.

[0011] The third object of the present invention is to provide a method for using a flux for smelting ultrafine scrap copper particles, that is, to provide a method for adding the flux to smelt ultrafine scrap copper particles to recover copper.

[0012] In order to solve the above first purpose, the present invention is achieved through the following technical solutions:

[0013] A flux for smelting ultrafine scrap copper particles, the flux components comprising by weight: 10%-50% aluminum fluoride AlF3, 10%-50% calcium fluoride CaF2, 5%-20% borax Na2B4O7, 10%-40% sodium carbonate Na2CO3; the balance is sodium chloride NaCl.

[0014] Aluminum fluoride AlF3, calcium fluoride CaF2: As the main components of flux, the addition of aluminum fluoride and calcium fluoride will act on the surface of copper particles to combine cuprous oxide (melting point 1235°C) and cupric oxide (melting point 1326°C) into copper fluoride for peeling off. In addition, copper fluoride has a low melting point (950°C), which is convenient for improving the fluidity of the ash. The addition of aluminum fluoride and calcium fluoride below 10% is not conducive to the complete reaction of copper oxide and cuprous oxide particles, and above 50% increases the viscosity and amount of the ash.

[0015] Sodium chloride NaCl, borax Na2B4O7: Since the melting point is around 700℃, a liquid film can be formed on the surface of molten copper to prevent the burning and volatilization of zinc. At the same time, it can form a coating and heat preservation effect on the copper sand to accelerate the melting process.

[0016] Sodium carbonate Na2CO3: As one of the main components of the solvent, it is mainly used in slag-making reaction. By forming corresponding sodium salts with the oxides in the ash, the ash becomes fluffy, which is conducive to the copper particles entering the copper water through the fluffy channels. If the proportion of sodium carbonate Na2CO3 is lower than 10%, the slag-making will be insufficient, the ash has high viscosity and high density, and the copper particles will be hindered from sliding off. If the proportion of sodium carbonate Na2CO3 is higher than 40%, it is easy to generate too much sodium salt, resulting in the problem of compaction.

[0017] Preferably, the flux components include, by weight percentage: 20%-50% aluminum fluoride AlF3, 20%-50% calcium fluoride CaF2, 5%-10% borax Na2B4O7, 10%-30% sodium carbonate Na2CO3; the balance is sodium chloride NaCl.

[0018] Further preferably, the flux components include, by weight percentage: 30%-50% aluminum fluoride AlF3, 30%-50% calcium fluoride CaF2, 5%-10% borax Na2B4O7, 10%-20% sodium carbonate Na2CO3; the balance is sodium chloride NaCl.

[0019] As mentioned above, aluminum fluoride AlF3 and calcium fluoride CaF2 are used to react with copper oxide and cuprous oxide to form copper fluoride for peeling, and at the same time improve the fluidity of the furnace ash. Because the present invention is to solve the smelting of ultrafine scrap copper particles, the copper particles are less than 0.1 mm, and the degree of surface oxidation is much higher than that of conventional scrap copper particles. Therefore, the amount of aluminum fluoride and calcium fluoride added to the flux here is also much larger, preferably more than 30%, which is more conducive to complete reaction with copper oxide and cuprous oxide, while more than 50% will increase the viscosity and amount of furnace ash.

[0020] The addition of sodium chloride NaCl and borax Na2B4O7 is conducive to the complete reaction of copper oxide and cuprous oxide.

[0021] Sodium carbonate Na2CO3: As mentioned above, it is mainly used for slagging reaction. It forms corresponding sodium salts with oxides in the ash and makes it fluffy, which is conducive to the copper particles entering the copper water through the fluffy channels. With a ratio of 10%-20%, the slag is fully formed and the ash is fluffy. At the same time, the sodium salt content is appropriate and there is no problem of compaction.

[0022] The technical solution adopted by the present invention to solve the above second purpose is: a method for preparing a flux for smelting ultrafine scrap copper particles, using the flux formula as mentioned above, and mixing aluminum fluoride, calcium fluoride, borax, sodium carbonate and sodium chloride evenly.

[0023] The technical solution adopted by the present invention to solve the above third purpose is: a method for using a flux for smelting ultrafine scrap copper particles, characterized in that the flux described above is used, and specifically includes the following steps: after the furnace is opened, a number of scrap bronzes are first added to the smelting furnace, and after melting, ultrafine scrap copper particles mixed with the flux are added, and intermittent stirring is performed to achieve the smelting of the ultrafine scrap copper particles.

[0024] The melting point of individual ultrafine scrap copper particles is high and they are not easy to melt. First, add some scrap bronze and use the low melting point of scrap bronze to pre-melt it. The molten copper water can quickly wrap the ultrafine scrap copper particles added later, and then quickly initiate the melting of the ultrafine scrap copper particles with the help of flux. The flux mainly includes a mixture of sodium fluoride AlF3, calcium fluoride CaF2, sodium chloride NaCl, borax Na2B4O7, and sodium carbonate Na2CO3 as raw materials. Mix them evenly and put them in a plastic bag for later use. Add them to the furnace. After the flux enters the slag, a series of chemical reactions will occur:

[0025] ZnO+Na2CO3→Na2O·ZnO+CO2.

[0026] CaF2+ CuO+ZnO→Ca2O·ZnO+CuF2.

[0027] AlF3+ CuO+ZnO→Al2O3·ZnO+CuF2.

[0028] Na2B4O7+ ZnO→Na2O·ZnO+B2O3·ZnO.

[0029] In the above reaction, Na2O·ZnO, Al2O3·ZnO, and B2O3·ZnO act as fluffy slag, which is conducive to copper particles falling into copper water. CaF2 and AlF3 reduce the melting point of slag, melt copper oxide and cuprous oxide, and are used to form the corresponding low-melting-point fluoride salt CuF2. CuF2 is a hard and brittle substance, which is used to peel off the copper oxide shell.

[0030] Preferably, a method for using a flux for smelting ultrafine scrap copper particles is characterized in that the amount of flux added is 2% to 2.5% of the total amount of the smelting furnace charge. The appropriate amount of flux allows complete smelting while saving raw materials.

[0031] Preferably, a method for using a flux for smelting ultrafine scrap copper particles is characterized in that the amount of scrap bronze added is 5% to 25% of the total amount of the smelting furnace charge. The appropriate amount of scrap bronze added ensures smooth melting without increasing the amount of other scrap copper.

[0032] Preferably, a method for using a flux for smelting ultrafine scrap copper particles is characterized in that the ultrafine scrap copper particles mixed with the flux are added in batches, and each batch of ultrafine scrap copper particles is added and then stirred evenly and ventilated, and then a corresponding amount of flux is added. After stirring, the next batch of ultrafine scrap copper particles and flux are added and stirred until all raw materials are completely smelted. Adding in batches facilitates complete smelting of copper sand without forming copper bags.

[0033] Preferably, a method for using a flux for smelting ultrafine scrap copper particles is characterized in that after adding a batch of ultrafine scrap copper particles mixed with flux, a slag remover is added to the furnace, and after stirring evenly, a refining agent is pressed into the copper water to stir and remove slag. The addition of the slag remover and the refining agent can improve the quality of the recovered copper ingots.

[0034] Preferably, a method for using a flux for smelting ultrafine scrap copper particles is characterized in that the slag remover is selected from at least one of sodium carbonate, silicon dioxide, sodium chloride, and borax, and the amount of the slag remover added is 0.25% to 1% of the total amount of the smelting furnace charge; the refining agent is selected from at least one of sodium carbonate, fluorite powder, cryolite, and dolomite, and the amount of the refining agent added is 0.25% to 1% of the total amount of the smelting furnace charge.

[0035] The beneficial effects of the present invention are as follows: the present invention introduces AlF3 into a conventional waste copper flux, increases the content ratio of aluminum fluoride and calcium fluoride at the same time, and then mixes with an appropriate amount of borax, sodium carbonate, and sodium chloride. The flux with the final ratio can reduce the melting point of the slag, and is helpful to completely react with the copper oxide and cuprous oxide on the ultrafine waste copper particles to generate hard and brittle copper fluoride for peeling off the copper oxide shell layer, thereby obtaining a method for smelting and recovering ultrafine waste copper particles with a high copper yield. Under the synergistic effect of these components, the flux can accelerate the flow of ultrafine waste copper particles into the pre-melted waste bronze copper water, and finally realize the smelting and recovery of ultrafine waste copper particles, and finally the recovery rate of ultrafine waste copper particles is efficiently improved. The method is safe and harmless and does not pose a health risk to operators.

[0036] The preparation method of the flux is simple and easy to operate.

[0037] The method for using the flux introduces pre-melting of scrap bronze, sets appropriate ultrafine scrap copper particles, the order of adding the flux, and the adding position, and utilizes the closed reduction space constructed by the flux to assist the reduction of copper oxide, thereby reducing the melting point of the scrap copper particles and realizing the smelting and recovery of the ultrafine scrap copper particles. The flux is used to reduce the melting point of the furnace ash slag and make the furnace ash slag fluffy, thereby efficiently improving the recovery rate of copper particles, and the method is easy to use. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0039] Figure 1 This is a sample picture of ultra-fine waste copper sand;

[0040] Figure 2 This is the ash slag sample after copper sand smelting in Example 1;

[0041] Figure 3 This is the furnace ash slag sample after copper sand smelting in Example 2;

[0042] Figure 4 This is the ash slag sample after copper sand smelting in Comparative Example 1. DETAILED DESCRIPTION

[0043] The terms used herein are only for describing specific embodiments and are not intended to limit the present invention. Unless the context gives an obviously opposite meaning, the singular form used herein is also intended to include the plural form. It should also be understood that the term "comprising" does not specifically refer to a certain characteristic, field, integer, step, action, element and / or component, but excludes the existence or addition of other characteristics, fields, integers, steps, actions, elements, components and / or groups. If a part is described as being on another part, other parts can be directly on the other part or there between. When a part is described as being directly on another part, there will be no other parts there between. Although not otherwise defined, the meaning of all terms used herein (including technical terms and scientific terms) is the same as that generally understood by technicians in the field. For terms defined in the dictionary, they should be interpreted as having a meaning consistent with the relevant technical literature and the content disclosed herein, and their meaning should not be interpreted in an idealized or overly formal sense.

[0044] The present invention is further described in detail below in conjunction with the embodiments of the accompanying drawings. However, the present invention can be implemented in various different ways and is not limited to the embodiments described herein.

[0045] Example 1

[0046] The flux ratio is: aluminum fluoride AlF3, 35wt%; calcium fluoride CaF2, 35wt%; borax Na2B4O7, 10wt%; sodium carbonate Na2CO3, 15wt%; sodium chloride NaCl, the rest. The amount of homemade flux added is 2.5wt% of the total amount of the charge.

[0047] The smelting raw materials are: 960kg of ultrafine scrap copper sand and 272kg of scrap bronze.

[0048] Table 1 Copper content in ultra-fine waste copper sand

[0049]

[0050] The smelting process is carried out in a 750kg medium frequency furnace as follows:

[0051] Step 1: Evenly mix the flux and ultrafine scrap copper sand, raise the furnace, add 272kg scrap bronze into the furnace, and add scrap copper sand in batches after melting. Add 100kg of copper sand each time for smelting, and set the power to 700V. Ventilate after smelting for 30 minutes to avoid the risk of holding air in the furnace, then stir evenly, add 5kg of flux at the same time, and after stirring, continue to add the next batch of 100kg of copper sand, and repeat the above process for continuous high-pressure insulation melting.

[0052] Step 2: After smelting 300kg of copper sand, add the slag remover into the furnace, stir evenly, then press the refining agent into the copper water, stir, and start slag removal. After the slag removal is completed, repeat step 1 and continue production until all the copper sand is smelted.

[0053] Step 3: After the smelting is completed, take the spectral sample for component testing, pour the molten copper into the sand mold, and complete the smelting process of the copper sand.

[0054] The raw copper ash (i.e., copper sand) and the product copper ingot component analysis results of this embodiment are shown in Table 2. It can be seen from the table that the copper ingot is mainly composed of copper, and its copper content is greatly increased compared with the raw copper ash, achieving the purpose of copper recovery. The production material input-output data of this embodiment are shown in Table 3. The slag remover in the table refers to the total amount of the slag remover and the refining agent mixed. The copper rate obtained in this embodiment is 43.54%.

[0055] Table 2 Ingredients of Example 1

[0056]

[0057] Table 3 Example 1 Production material input and output table

[0058]

[0059] The actual pictures of raw copper sand and slag after smelting are as follows: Figure 1 , Figure 2 As shown, through Figure 2 The analysis shows that the ash slag in Example 1 has large slag blocks, indicating that the copper sand is melted and a large amount of slag blocks are formed during smelting, and the copper yield reaches 43.54%.

[0060] Example 2

[0061] The flux ratio is: aluminum fluoride AlF3, 40wt%; calcium fluoride CaF2, 40wt%; borax Na2B4O7, 10wt%; sodium carbonate Na2CO3, 10wt%; sodium chloride NaCl, the rest. The amount of homemade flux added is 2.5wt% of the total amount of the charge.

[0062] The smelting raw materials are: 924kg of ultra-fine scrap copper sand and 50kg of scrap bronze.

[0063] The smelting process is carried out in a 750kg medium frequency furnace as follows:

[0064] Step 1: Evenly mix the flux and ultrafine scrap copper sand, raise the furnace, add 50kg of scrap bronze into the furnace, and add scrap copper sand in batches after melting. Add 100kg of copper sand each time for smelting, and set the power to 700V. Ventilate after smelting for 30 minutes to avoid the risk of holding air in the furnace, then stir evenly, add 5kg of flux at the same time, and after stirring, continue to add the next batch of 100kg of copper sand, and repeat the above process for continuous high-pressure insulation melting.

[0065] Step 2: After smelting 300kg of copper sand, add the slag remover into the furnace, stir evenly, then press the refining agent into the copper water, stir, and start slag removal. After the slag removal is completed, repeat step 1 and continue production until all the copper sand is smelted.

[0066] Step 3: After the smelting is completed, take the spectral sample for component testing, pour the molten copper into the sand mold, and complete the smelting process of the copper sand.

[0067] The raw material copper ash (i.e., copper sand) and the product copper ingot component analysis results of this embodiment are shown in Table 4. It can be seen from the table that the copper ingot is mainly composed of copper, and its copper content is greatly increased compared with the raw material copper ash, achieving the purpose of copper recovery. The production material input-output data of this embodiment are shown in Table 5. The slag remover in the table refers to the total amount of the slag remover and the refining agent mixed. The copper rate obtained in this embodiment is 48.38%.

[0068] Table 4 Ingredients of Example 2

[0069]

[0070] Table 5 Example 2 Production material input and output form

[0071]

[0072] The actual pictures of raw copper sand and slag after smelting are as follows: Figure 1 , Figure 3 As shown, through Figure 3 The analysis showed that the ash slag in Example 2 had large slag blocks, the copper sand was melted, and the copper yield reached 48.38%.

[0073] Comparative Example 1

[0074] The smelting raw materials are: 1012kg of ultrafine scrap copper sand and 214kg of scrap bronze.

[0075] The smelting process is carried out in a 750kg medium frequency furnace as follows:

[0076] Step 1: Raise the furnace, add 214kg of scrap bronze into the furnace, and add scrap copper sand in batches after melting. Add 100kg of copper sand each time for smelting, and set the power to 700V. After smelting for 30 minutes, ventilation is required to avoid the risk of holding air in the furnace, and then stir evenly. After stirring, continue to add the next batch of 100kg of copper sand, and repeat the above process for continuous high-pressure insulation melting.

[0077] Step 2: After smelting 300kg of copper sand, add the slag remover into the furnace, stir evenly, then press the refining agent into the copper water, stir, and start slag removal. After the slag removal is completed, repeat step 1 and continue production until all the copper sand is smelted.

[0078] Step 3: After the smelting is completed, take the spectral sample for component testing, pour the molten copper into the sand mold, and complete the smelting process of the copper sand.

[0079] The composition analysis results of the raw copper ash (i.e., copper sand) and the product copper ingot of this embodiment are shown in Table 6. It can be seen from the table that the copper ingot is mainly composed of copper, and its copper content is greatly increased compared with the raw copper ash. However, from the production material input-output table of Comparative Example 1 in Table 7, it can be seen that since only waste bronze is added without adding flux, the output of the copper ingot of this comparative example is very small, and the copper output rate is only 9.88%, which makes it difficult to achieve the purpose of copper recovery.

[0080] Table 6 Ingredients of Comparative Example 1

[0081]

[0082] Table 7 Comparative Example 1 Production Material Input and Output Form

[0083]

[0084] The actual pictures of raw copper sand and slag after smelting are as follows: Figure 1 , Figure 4 As shown, through Figure 4 Analysis shows that the ash slag in this comparative example rarely contains large slag pieces, and the ash slag is basically in the form of fine copper sand. Most of the copper sand in the raw material is not melted, and the final copper yield is only 9.88%, which fails to achieve the effect of copper recovery.

[0085] Comparative Example 2

[0086] The smelting raw materials are: 961 kg of ultra-fine scrap copper sand.

[0087] The smelting process is carried out in a 3000kg medium frequency furnace as follows:

[0088] Step 1: Raise the furnace, add copper powder and waste copper sand, and add 961kg of waste copper sand in batches. Add 100kg of copper sand each time for smelting, and set the power to 700V. After smelting for 30 minutes, ventilation is required to avoid the risk of holding air in the furnace, and then stir evenly. After stirring, continue to add the next batch of copper sand 100kg, and repeat the above process for continuous high-pressure insulation melting.

[0089] Step 2: After smelting 300 kg of copper sand, stir it evenly, then press the refining agent into the copper water, stir it, and start slag removal. After the slag removal is completed, repeat step 1 and continue production until all the copper sand is smelted.

[0090] Step 3: After smelting is completed, take the spectral sample for composition testing. If the composition is unqualified, it needs to be adjusted until the composition is qualified. Then transfer the molten copper to the holding furnace for normal traction operation.

[0091] The raw material copper ash (i.e., copper sand) and the product copper ingot composition analysis results of this embodiment are shown in Table 8. Since the quality of the molten copper after smelting does not meet the casting requirements, the molten copper is treated by traction operation in this comparative example, and no copper ingot is produced. From the production material input-output table of comparative example 1 in Table 9, it can be seen that since no waste bronze and flux are added, no copper ingot is produced in this comparative example, and the copper output rate is only 8.84%, which makes it difficult to achieve the purpose of copper recovery.

[0092] Table 8 Ingredients of Comparative Example 2

[0093]

[0094] Table 9 Comparative Example 2 Production Material Input and Output Form

[0095]

Claims

1. A method for using a flux for smelting ultrafine scrap copper particles, characterized in that: The flux components include, by weight percentage: 30%-50% aluminum fluoride AlF3, 30%-50% calcium fluoride CaF2, 5%-10% borax Na2B4O7, 10%-20% sodium carbonate Na2CO3; the balance is sodium chloride NaCl; The method specifically comprises the following steps: after the furnace is opened, a number of scrap bronzes are first added into the smelting furnace, after melting, ultrafine scrap copper particles mixed with flux are added, and stirring is performed intermittently to achieve smelting of the ultrafine scrap copper particles.

2. The method for using a flux for smelting ultrafine scrap copper particles according to claim 1, characterized in that: Aluminum fluoride, calcium fluoride, borax, sodium carbonate and sodium chloride are uniformly mixed to obtain a flux.

3. The method for using a flux for smelting ultrafine scrap copper particles according to claim 1, characterized in that: The amount of flux added is 2% to 2.5% of the total amount of the smelting furnace charge.

4. The method for using a flux for smelting ultrafine scrap copper particles according to claim 1, characterized in that: The amount of the waste bronze added is 5% to 25% of the total amount of the smelting furnace charge.

5. The method for using a flux for smelting ultrafine scrap copper particles according to claim 1, characterized in that: The ultrafine scrap copper particles mixed with flux are added in batches. After each batch of ultrafine scrap copper particles is added, they are uniformly stirred and ventilated, and then a corresponding amount of flux is added. After stirring, the next batch of ultrafine scrap copper particles and flux are added and stirred until all raw materials are completely smelted.

6. The method for using a flux for smelting ultrafine scrap copper particles according to claim 1, characterized in that: After adding some batches of ultrafine scrap copper particles mixed with flux, add slag remover into the furnace, stir evenly, press refining agent into copper water, stir and remove slag.

7. The method for using a flux for smelting ultrafine scrap copper particles according to claim 6, characterized in that: The deslagging agent is selected from at least one of sodium carbonate, silicon dioxide, sodium chloride, and borax, and the amount of the deslagging agent added is 0.25% to 1% of the total amount of the smelting furnace charge; the refining agent is selected from at least one of sodium carbonate, fluorite powder, cryolite, and dolomite, and the amount of the refining agent added is 0.25% to 1% of the total amount of the smelting furnace charge.

Citation Information

Patent Citations

  • Fluxing agent for smelting scrap brass particles as well as preparation method and use method of fluxing agent

    CN116949312A

  • FLUX composition for copper-based alloys

    WO2023038591A1